1989
DOI: 10.1017/s0016672300028627
|View full text |Cite
|
Sign up to set email alerts
|

RelAmutation and pBR322 plasmid amplification in amino acid-starved cells ofEscherichia coli

Abstract: Plasmid pBR322 is amplified following amino-acid limitation in Escherichia coli rel A hosts. In rel A* hosts there was no significant amplification or a much smaller one. Plasmid amplification is due to the relA mutation; when the relA + allele is transferred into the relA mutant CP79 this strain no longer amplifies plasmid DNA during amino acid starvation. It is concluded that ppGpp is a negative effector of plasmid replication. Amplification is temperature dependent, being maximal at 32 °C and negligible at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…However, they could not increase significantly the production of figlucanase. Riethdorf et al (1989) and Wegrzyn (1995) repoited the lowest amplification efficiency at elevated temperatures for pBR322 and L plasmids, respectively. Here we demonstrate plasmid DNA degradation at elevated temperatures after prolonged amino acid starvation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they could not increase significantly the production of figlucanase. Riethdorf et al (1989) and Wegrzyn (1995) repoited the lowest amplification efficiency at elevated temperatures for pBR322 and L plasmids, respectively. Here we demonstrate plasmid DNA degradation at elevated temperatures after prolonged amino acid starvation.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that the amplification efficiency depends on the kind of replicon, the nature of deprived amino acid, and the cultivation temperature (Riethdorf et al, 1989;Herman et al, 1994a;Wegrzyn, 1995). In both cases (ColEl and h plasmids) the lowest amplification efficiency was observed at elevated temperatures (above 37OC and above 4OoC, respectively).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The starvation for most amino acids resulted in inhibition of plasmid DNA replication in reiA+ but not in relA-strains (HECKER et a]. 1983, 1985, HERMAN et al 1994a, b, HOFMANN et al 1990, RIETHDORF et al 1989, WI~GRZYN et al 1991a. However, in some cases, ColEl plasmids replicated also in amino acid-starved wild type strains (LIN-CHAO andBREMER 1986, HERMAN et al 1994a, b).…”
Section: Cole1mentioning
confidence: 99%
“…Since it was reported previously that replication of different plasmids during stringent and relaxed response may depend on the nature of the deprived amino acid and on temperature [9, 10, 18], we investigated the replication of λ plasmid DNA in relA + and relA − strains of E. coli starved for different amino acids at different temperatures. Bacteria harboring λ plasmids were grown in minimal medium and starved for a certain amino acid.…”
Section: Resultsmentioning
confidence: 99%